HUBUNGAN EFEK SAMPING OBAT DENGAN KEPATUHAN MINUM OBAT PADA PASIEN TUBERKULOSIS DI WILAYAH KERJA PUSKESMAS KUNIR - Zainal Abidin; Rizka Yunita; Shafia Annisa (Universitas Muhammadiyah Jember, 2022)
Tuberculosis is a disease caused by Mycobacterium tuberculosis. Tuberculosis has quite serious problems, especially in the emergence of side effects of Anti Tuberculosis Drugs (OAT). Successful therapy of this disease depends on combination drugs for at least 6 months.The design in this study uses qualitative research with analytical survey methods used to try to find out the health phenomenon that occurs. The data collection instrument in this study was interviewed using checklists. The checklist consists of 6 questions about drug side effects and 8 questions about medication adherence. The questionnaire used to determine the compliance of patients with hypertension was the Morisky Medication Adherence Scale (MMAS).Based on the results of this study, it was found that almost all respondents were obedient in taking tuberculosis drugs as many as 45 respondents (97.8%). This compliance is based on the fact that the Kunir Health Center is successful in providing optimal service to the community in the working area of the Kunir Health Center, but this cannot be separated from the respondents whose education is almost half of high school graduates where high school graduates have fairly good knowledge in receiving information obtained from staff. health, media, or closest relatives, besides that in this study almost half of the respondents are also young so their willingness to recover is high, this of course will also make less willingness to heal from other sufferers to join groups that are more in implementing drinking compliance tuberculosis drugs.Keywords: Tuberculosis, Drug Side Effects, Medication ComplianceTuberculosis is a disease caused by Mycobacterium tuberculosis. Tuberculosis has quite serious problems, especially in the emergence of side effects of Anti Tuberculosis Drugs (OAT). Successful therapy of this disease depends on combination drugs for at least 6 months.The design in this study uses qualitative research with analytical survey methods used to try to find out the health phenomenon that occurs. The data collection instrument in this study was interviewed using checklists. The checklist consists of 6 questions about drug side effects and 8 questions about medication adherence. The questionnaire used to determine the compliance of patients with hypertension was the Morisky Medication Adherence Scale (MMAS).Based on the results of this study, it was found that almost all respondents were obedient in taking tuberculosis drugs as many as 45 respondents (97.8%). This compliance is based on the fact that the Kunir Health Center is successful in providing optimal service to the community in the working area of the Kunir Health Center, but this cannot be separated from the respondents whose education is almost half of high school graduates where high school graduates have fairly good knowledge in receiving information obtained from staff. health, media, or closest relatives, besides that in this study almost half of the respondents are also young so their willingness to recover is high, this of course will also make less willingness to heal from other sufferers to join groups that are more in implementing drinking compliance tuberculosis drugs.